EROTISME DALAM KUMPULAN CERPEN JANGAN MAIN-MAIN (DENGAN KELAMINMU) KARYA DJENAR MAESA AYU (ANALISIS KAJIAN SEMANTIK) - Lubis, Masyithoh Fitri Asman; Elmustian, Elmustian; Hermandra, Hermandra (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research entitled Erotism in the Collection of Short Story Do Not Plays (with Your Sex) By Djenar Maesa Ayu (Analysis of Semantic). The purpose of this research is to describe the words that contain elements of erotism in the Collection of Short Story Do Not Plays (with Your Sex) By Djenar Maesa Ayu (Analysis of Semantic), and describe the meaning of the figurative word that contain elements of erotism in the Collection of Short Story Do Not Plays (with Your Sex) By Djenar Maesa Ayu (Analysis of Semantic) in the form of 22 two figurative words. The results of this study were obtained after classifying word data containing erotic elements. Then analyzed using semantic study of the word kias containing erotic elements. The result is found that the element of erotism in the Collection of Short Story Do Not Plays (with Your Sex) By Djenar Maesa Ayu (Analysis of Semantic) pinned as an addition to aesthetics literary works and as an adder taste of the of literary works.Keywords: Erotism, Short story, Art, Semantic